Integrated Face Recognition and IoT-Based Electronic Equipment Management System - Firdayanti Firdayanti; Riyo Putra Syam Satria; Nanda Octavia; Muhammad Danang Mukti Darmawan; Mohamad Alvin Renaldi; Ivan De Nerol; Fiqri Nurfadillah; Fiona Kharismatunnisaa; Ester Angeline; Yourdan Saputra (Batrisya Education, 2024)
This research explores the development of an Integrated Face Recognition and IoT-Based Electronic Equipment Management System, aiming to enhance security and efficiency in equipment lending processes. Utilizing face recognition technology integrated with IoT, the system is designed to automate and secure the return of borrowed electronic equipment. The methodology includes a detailed study of existing management practices, development of a prototype system, and analysis of its effectiveness in a real-world setting. Results indicate a significant improvement in the management and security of equipment lending. The system demonstrates potential for broader application in similar contexts.